Alteration of primary cilia morphology and associated signalling in ameloblastoma - Filušová, Jana; Putnová, Iveta; Hurník, Pavel; Daněk, Zdeněk; Macháček, Ctirad; Jan Štembírek; Buchtová, Marcela; Moldovan Putnová, Barbora (Archives of oral biology, 2022)
OBJECTIVES: Primary cilium is a cellular organelle with growing significance confirmed in tumour biology. Primary cilia have been associated with fine tuning of numerous cell signalling pathways and the role of this structure in cancer initiation and progression is recently at the forefront of attention. Here, we investigated possible alterations in the occurrence of primary cilia and changes of associated signalling in ameloblastoma, which represents the most common odontogenic tumour. METHODS: We performed immunohistochemistry to assess the number and morphology of primary cilia in ameloblastoma tissues. The gene expression of key SHH pathway members was analysed by qPCR. As a functional experiment, we treated a primary ameloblastoma cell line by a SHH pathway inhibitor Sonidegib (LDE225). RESULTS: We uncovered differences in primary cilia distribution and appearance in histological subtypes of ameloblastoma with the highest number of ciliated cells in plexiform and follicular subtypes. SHH protein was located close to primary cilia in ameloblastoma epithelial cells and the expression of molecules downstream of SHH signalling was upregulated. Moreover, the inhibition of SHH pathway by Sonidegib caused downregulation of SHH effector gene GLI1 and cell cycle regulator CCND1 in ameloblastoma primary cell line. The inhibition of SHH signalling also altered the expression of molecules involved in intraflagellar transport. CONCLUSIONS: In conclusion, our study uncovered alterations in number of ciliated cells and associated signalling in ameloblastoma, which indicate SHH inhibitors as potential therapeutic target to treat this disease.
Keywords: Hedgehog Proteins; cilie; signální transdukce; IFT; odontogenní nádory; Cilia; ameloblastom; Primary cilia; SHH; lidé; Odontogenic Tumors; proteiny hedgehog; Ameloblastoma; Humans; Signal Transduction